A dicoumarol-graphene oxide quantum dot polymer inhibits porcine reproductive and respiratory syndrome virus through the JAK-STAT signaling pathway - Li, Zhuowei; Wang, Junjun; Wang, Siyu; Zhao, Wei; Hou, Xiaolin; Wang, Jianfang; Dong, Hong; Zhou, Shuanghai; Gao, Yuan; Yao, Wei; Li, Huanrong; Liu, Xuewei (Frontiers in Microbiology, 2024)
Porcine reproductive and respiratory syndrome virus (PRRSV) causes substantial economic losses in the global swine industry. The current vaccine options offer limited protection against PRRSV transmission, and there are no effective commercial antivirals available. Therefore, there is an urgent need to develop new antiviral strategies that slow global PRRSV transmission. In this study, we synthesized a dicoumarol-graphene oxide quantum dot (DIC-GQD) polymer with excellent biocompatibility. This polymer was synthesized via an electrostatic adsorption method using the natural drug DIC and GQDs as raw materials. Our findings demonstrated that DIC exhibits high anti-PRRSV activity by inhibiting the PRRSV replication stage. The transcriptome sequencing analysis revealed that DIC treatment stimulates genes associated with the Janus kinase/signal transducer and activator of transcription (JAK/STAT) signalling pathway. In porcine alveolar macrophages (PAMs), DIC-GQDs induce TYK2, JAK1, STAT1, and STAT2 phosphorylation, leading to the upregulation of JAK1, STAT1, STAT2, interferon-β (IFN-β) and interferon-stimulated genes (ISGs). Animal challenge experiments further confirmed that DIC-GQDs effectively alleviated clinical symptoms and pathological reactions in the lungs, spleen, and lymph nodes of PRRSV-infected pigs. These findings suggest that DIC-GQDs significantly inhibits PRRSV proliferation by activating the JAK/STAT signalling pathway. Therefore, DIC-GQDs hold promise as an alternative treatment for PRRSV infection.